Apakah Psychological Contract Memengaruhi Safety Behavior? Kajian pada Karyawan di Industri Kelapa Sawit - Juniarly, Amalia; Eprisa, Amelia Sesariska (Fakultas Psikologi Universitas YARSI, 2024)
Data showed that many employees working in the palm oil industry experienced many work accidents. This indicates a lack of practice in employee safety behaviour at the plantation company. The psychological contract is one of the factors that influence safety behaviour. This research aimed to see the influence of psychological contracts on safety behaviour among employees in the palm oil industry. This research involved 229 harvesting employees in the palm oil industry who were hired using a purposive sampling technique. The scale used was the safety behaviour and psychological contract scale. The data was analyzed using simple linear regression analysis, showing that the research hypothesis was accepted. Psychological contracts have a significant influence on safety behaviour (R2 = 0.414; F (1, 228) = 160.476; p < 0.05) in palm oil industry employees. This shows the importance of psychological contracts in reducing the number of work accidents for plantation employees.